New Method of Vaccination Against Anthrax - A. N. Shevtsov; S. A. Permyakov; N. G. Khapaev; R. Sh. Ziganshin (Проблемы особо опасных инфекций, 2023)
The aim of this work was to develop an oral method of vaccination against anthrax, since wide vaccination campaigns using this method require no special conditions, equipment, and instruments. Also, minimum number of medical personnel is sufficient to ensure control over the intake of the drug. Materials and methods. Domestic raw materials, consumables and reagents that passed the incoming inspection and met the requirements of State and industry standards, technical specifications, and the articles of the Pharmacopoeia were used for the work. Batches of anthrax vaccines based on Bacillus anthracis strain STI-1, manufactured at the Research Center (Kirov) of the “48th Central Research Institute” of the Ministry of Defense of Russia were put to the test. Results and discussion. The immunization schemes have been tested on animals, taking into account the features of the antigen. One of the crucial factors that determine the effectiveness of oral vaccination is the correct choice of the type and form of the oral anthrax vaccine administered enterally. It has been shown that in contrast to oral vaccines, the vaccine strain in enteral vaccines must be protected from the harmful effects of stomach contents. Thus, enteric-coated capsules coated with a shell that is resistant to the action of stomach acid were used for the study. The presented experimental data indicate that a single administration of the capsules with oral anthrax vaccine STI protects at least 70 % of laboratory animals from a highly virulent strain of the anthrax microbe and confirm the safety and non-reactogenicity of the drug. The developed laboratory technology makes it possible to obtain a finished product containing one inoculation dose of an oral vaccine for laboratory animals. So, a new method of vaccination has been designed. It is necessary to conduct preclinical and clinical trials to promptly introduce the oral administration of anthrax vaccine into medical practice as the simplest method for mass vaccination of humans.